Analisis Manajemen Peserta Didik dalam Optimalisasi Minat dan Bakat melalui Kegiatan Ekstrakurikuler di SMA Negeri Samarinda - Bulantari, Dinda Ayu; Suryani, Yeni; Wijiati, Luluk; Warman, Warman (Lembaga Yasin AlSys, 2025)
This study aims to analyze the effectiveness of POAC-based student management (Planning, Organizing, Actuating, and Controlling) in optimizing students' interests and talents through extracurricular activities at Samarinda State High School. The research method used is descriptive quantitative with multiple linear regression analysis, which measures the influence of each POAC dimension on the optimization of students' interests and talents. The results showed that Actuating had the most dominant influence on extracurricular success (β = 0.41; p < 0.001), indicating that sustainability and interactivity of activities contributed significantly to the development of students' skills. Meanwhile, Controlling had a negligible influence (β = 0.12; p > 0.05), indicating a weak system for evaluating and monitoring extracurricular results. In terms of participation, the survey results show that sports and arts extracurricular activities are the top choice for students (35% and 30%), while the science/academic and social/religious fields have lower participation rates. In addition, the frequency of student involvement is still limited, with the majority of students only participating in 1–2 extracurricular activities. This is allegedly caused by the academic burden and lack of socialization regarding extracurricular benefits. As a recommendation, schools need to diversify extracurricular programs, implement more flexible scheduling, and strengthen data-based evaluation systems to increase the effectiveness of activities. Collaboration with professional trainers and educational institutions is also a strategy that can be applied to improve the quality of coaching. With a more structured and innovative management, extracurricular activities at SMA Negeri Samarinda are expected not only to run actively but also to have a real impact on the development of students' interests, talents, achievements, and character.